Pendidikan Kristiani dalam mewujudkan pembangunan berkelanjutan: Interseksionalitas pemikiran Dietrich Bonhoeffer tentang relasi sosial-ekonomi - Sumarno, Yuel (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2025)
This study examines the role of Christian education in realizing sustainable development, particularly in the socio-economic dimension re-lated to SDG 1 (No Poverty), SDG 8 (Decent Work and Economic Growth), and SDG 10 (Reduced Inequalities). Using an intersectional approach, this research examines the role of Christian education in shaping character, promoting economic self-reliance, and fostering social cohesion. Dietrich Bonhoeffer’s concepts of Stellvertretung (vicarious responsibility) and being-for-others serve as the theological framework to underscore the pu-blic dimension of Christian faith. The findings suggest that Christian edu-cation can serve as a transformative agent, integrating faith, practical skills, work ethics, and social solidarity. Vocational education, the empowerment of vulnerable groups, and the formation of ethical leadership establish Christian education as a strategic means of addressing inequality, struc-tural poverty, and marginalization. Accordingly, the proposed new para-digm is that sustainable development should not rely solely on economic growth but must also integrate spirituality and social justice. Abstrak Penelitian ini menelaah peran pendidikan Kristiani dalam me-wujudkan pembangunan berkelanjutan, khususnya pada dimensi sosial-ekonomi yang berhubungan dengan SDGs 1 (No Poverty), SDGs 8 (Decent Work and Economic Growth), dan SDGs 10 (Reduced Inequalities). Dengan me-nggunakan pendekatan interseksional, penelitian ini mengkaji kontribusi pendidikan Kristen dalam membentuk karakter, memperkuat kemandi-rian ekonomi, dan membangun kohesi sosial. Pemikiran Dietrich Bonhoef-fer tentang Stellvertretung (tanggung jawab perwakilan) dan being-for-others (hidup bagi orang lain) dijadikan kerangka teologis untuk menegas-kan dimensi publik iman Kristen. Hasil penelitian menunjukkan bahwa pendidikan Kristiani dapat menjadi agen transformatif yang mengintegra-sikan iman, keterampilan praktis, etika kerja, dan solidaritas sosial. Pendi-dikan vokasional, pemberdayaan kelompok rentan, dan pembentukan ke-pemimpinan etis menjadikan pendidikan Kristiani sarana strategis untuk mengatasi ketimpangan, kemiskinan struktural, dan marginalisasi. De-ngan demikian, paradigma baru yang ditawarkan adalah pembangunan berkelanjutan tidak semata bertumpu pada pembangunan ekonomi, tetapi juga pada integrasi spiritualitas dan keadilan sosial.